The salt-free nickel-catalysed α-allylation reaction of ketones with allyl alcohol and diallylether. Issue 3 (22nd January 2020) - Mouhsine, Bouchaib; Karim, Abdallah; Dumont, Clément; Sauthier, Mathieu
Abstract : The alpha-allylation of ketones will allyl alcohol was performed thanks to the use of nickel-based catalysts. No base nor additive needed! Abstract : The nickel-catalysed α-allylation of ketones with allyl alcohol and diallylether has been performed under neutral conditions. As no base is involved, the products are synthesized without salts as side products. The dppf/Ni(cod)2 catalytic system in MeOH at 80 °C has been shown as the most effective reaction system to afford tetrasubstituted derivatives from various cyclic and acyclic ketones with one or two mobile protons. This process combined with a metathesis step yields spirocyclic compounds according to a salt free synthetic sequence.